Cytochemical study of Rhodnius neglectus and Rhodnius prolixus salivary gland cells (Hemiptera, Triatominae) - Anhê, Ana C. B. M. [UNESP]; Lima-oliveira, Ana P. M. [UNESP]; Azeredo-oliveira, Maria T. V. [UNESP] (Fundação Zoobotânica do Rio Grande do Sul, 2014)
Triatomines are hematophagous bugs of medical interest in South and Central America, where they may act as invertebrate hosts of the hemoflagellate protozoa Trypanosoma cruzi (the causative of Chagas’ disease) and Trypanosoma rangeli (Tejera, 1920). Triatomines of Rhodnius genus have salivary gland formed by two close and independent units: the principal and the accessory. This gland secretes saliva that abounds in substances that facilitate and permit feeding. Despite this importance, there are few reports on its cytochemistry. In purpose of amplifying this understanding, in this work it was investigated the nuclear structures (chromatin and nucleolar corpuscles) of salivary gland cells of Rhodnius neglectus (Lent, 1954) and Rhodnius prolixus (Stål, 1859). The salivary glands were removed from adult insects, fixed and submitted to different cytochemical methods: lacto-acetic orcein, silver ion impregnation, Feulgen reaction, Toluidine Blue, Variant method of critical electrolyte concentration and C-banding. The results evidenced predominance of binucleated cells, with bulky and polyploid nucleus, decondensed chromatin and a large nucleolar area. In addition, cytoplasmic metachromasy and a clear association between nucleolar and heterochromatic corpuscles were observed. Such characteristics were associated with intense synthesis activity to produce saliva. Besides, the heterochromatic corpuscles observed with C Banding permitted the differentiation of sexes and species.

Os triatomíneos são insetos hematófagos que apresentam interesse médico nas América do Sul e Central por serem hospedeiros invertebrados dos protozoários hemoflagelados Trypanosoma cruzi (agente etiológico da doença de Chagas) e Trypanosoma rangeli (Tejera, 1920). Os triatomíneos do gênero Rhodnius possuem glândula salivar formada por duas unidades próximas e independentes: a principal e a acessória. Esta glândula secreta uma saliva que contém substâncias que facilitam e permitem a hematofagia. Entretanto, apesar da sua importância, poucos estudos realizaram sua análise citoquímica. No propósito de ampliar esse entendimento, neste trabalho foram investigadas as estruturas nucleares (cromatina e corpúsculos nucleolares) das células da glândula salivar de Rhodnius neglectus (Lent, 1954) e Rhodnius prolixus (Stål, 1859). As glândulas foram removidas de insetos adultos, fixadas e submetidas a diferentes métodos citoquímicos: Orceína Lacto-Acética, Impregnação por Íons de Prata, Reação de Feulgen, Azul de Toluidina, Variante da Concentração Eletrolítica Crítica e Bandamento C. Os resultados evidenciaram predomínio de células binucleadas, com núcleos volumosos e poliplóides, cromatina descondensada e uma grande área nucleolar. Além disso, foi observada metacromasia citoplasmática e uma clara associação entre os corpúsculos nucleolares e heterocromáticos. Tais características foram associadas às atividades de intensa síntese proteica para a produção de saliva. Além disso, os corpúsculos heterocromáticos observados no Bandamento C permitiram a diferenciação dos sexos e das espécies.
Estudo citoquímico de células da glândula salivar de Rhodnius neglectus e Rhodnius prolixus (Hemiptera, Triatominae)
Keywords: Glândula; morfologia; cromatina; nucléolo; núcleo; Gland; morphology; chromatin; nucleolus; nucleus